RESPONS PERTUMBUHAN DAN HASIL SEMANGKA TANPA BIJI (Citrullus vulgaris Schrad) TERHADAP BEBERAPA JENIS MULSA - Faridatul Mukminah; Eddy Usman; Galih Prasetyo (Jurnal Agroekoteknologi, 2013)
This study aims to observe the effect of various types of mulch on the growth and yield of seedless watermelon (Citrullus vulgaris Schard). Implementing research in farmers' fields Scales Village, District Indralaya, Ogan Ilir, with a height ranging from 4-22 m above sea level, from February to April 2012. Research design using randomized block design, consisting of five treatments and five replications. The treatments were P0 = control (without mulch), P1 = use black-silver plastic mulch, P2 = use black plastic mulch, mulch P3 = using reeds as mulch as 0.8 kg of dry weight per m², P4 = use corn stalks mulch 2.6 kg dry weight per m². Parameters observed that the length of plant, days to flowering, fruit diameter, mean fruit weight, fruit weight per plant, fruit weight ha-1 (yield), wet biomass, and weight of wet roots. Black-silver plastic mulch influenced better on the growth and yield of seedless watermelon, compared with the other mulch and can increase the production of fruit namely the fruit weight/plant of 10.15 kg or 20.3 tons ha-1.